Design and psychometric of sexual self-care questionnaire in reproductive age women based on Waltz model - Fereshteh Yazdani; Masoumeh Simbar; Elham Zare; Zeinab HamzehGardeshi; Malihe Nasiri (Mashhad University of Medical Sciences, 2023)
Introduction: Designing valid and reliable tool to measure the sexual self-care status of reproductive age women in order to identify the strengths and weaknesses and design appropriate interventions to improve the sexual health status of reproductive age women is considered a necessity for the society. Therefore, this study was conducted with aim of designing and psychometrically evaluating sexual self-care questionnaire in women of reproductive age. Methods: This was a methodological study with a cross-sectional design conducted in 2021. A questionnaire was designed using a comparative approach based on the Waltz model. Then, to check the psychometric characteristics of the tool, quantitative and qualitative face validity and quantitative and qualitative content validity were investigated. Finally, the reliability of the tool was assessed by the internal consistency assessment and determining the Cronbach's alpha coefficient, and the stability assessment by the test-retest method and determining the intra-cluster correlation coefficient (ICC). Results: The final version of this questionnaire was designed with 40 items in four areas including prevention of sexually transmitted diseases and genital infections, prevention of gynecology cancers, prevention of unwanted pregnancy and promotion of sexual health. The psychometric characteristics of this questionnaire showed that the validity index of the total tool was 0.93 and the validity ratio of the total tool was 0.96. The relative reliability of the total tool was also shown with Cronbach's alpha of 0.94. The stability of the tool was also shown by the ICC in the total tool of 0.97 with a confidence interval of 0.94-0.98.  Conclusion: The Female Sexual Health Self-care (FSHS) questionnaire has acceptable validity and reliability in the Iranian population, which can measure the broad concept of sexual self-care. The results of this study can be available to experts and planners to review the current situation and design suitable interventions.